The Correlation Between Coworker Envy and Workplace Ostracism: The Mediating Role of The Nature of Work on the Job Performance of CV Istana Boneka Employees - Millenia Wahyu Wulan Ramadhani; Widi Dewi Ruspitasari (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2022)
This study aims to determine the effect of coworker envy and workplace ostracism on job performance, with the nature of work as a mediating variable. To achieve this goal, the researcher uses explanatory research with a quantitative approach. The sampling technique used is saturated sampling. Researchers get a sample of 35 respondents who are all employees of CV. Malang Puppet Palace. Data collection was carried out using a questionnaire. Then the data was processed using the Structural Equation Model (SEM) method with the SmartPLS analysis tool. The results showed that coworker envy and workplace ostracism had a positive effect on job performance. Meanwhile, coworker envy and workplace ostracism have a positive and significant effect on job performance. The nature of work has a positive and significant effect on job performance. It was found that the nature of work was able to mediate coworker envy significantly on job performance but not significantly on workplace ostracism on job performance.